PARTISIPASI MASYARAKAT TERHADAP PENGELOLAAN DAERAH ALIRAN SUNGAI (DAS) KRUENG ACEH DI KECAMATAN ULEE KARENG KOTA BANDA ACEH - Humairah, Hanifah; Zalmita, Novia (Program Studi Pendidikan Geografi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Samudra, 2024)
With the existence of the Krueng Aceh watershed, it is very helpful for the economy of the Kec, Ulee Kareng, especially the people who utilize the watershed as their livelihood. The purpose of this study was to determine the extent of community participation in managing the Krueng Aceh watershed Kec, Ulee Kareng. To achieve the research objectives, 23 responses were included who manage the watershed and live in the Kec, Ulee Kareng. This research uses a quantitative descriptive approach in order to be able to percentage and describe the level of community participation. Data collection was carried out by distributing questionnaires to respondents based on Arnstein's eight ladders of participation so that it could be categorized into high levels of participation. From the results of data processing, it was found that the participation indicators were at the partnership and delegation of power levels. In the study, the highest percentage was 20% at the level of community power and the lowest percentage was 5% at the level of anger management. Based on this data, the community that manages the Krueng Aceh watershed in Ulee Kareng Sub-district, Banda Aceh City participates in maintaining the watershed.